2015
DOI: 10.1590/1983-40632015v4536733
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de larvas de Helicoverpa armigera(Hübner) (Lepidoptera: Noctuidae) em diferentes fontes alimentares

Abstract: RESUMO Recentemente observada no Brasil, Helicoverpa armigera tornou-se praga relevante, tanto pela rápida disseminação como pela importância econômica das culturas nas quais se estabeleceu, como a soja e o milho. A compreensão do processo de estabelecimento em diferentes regiões e sistemas de produção e da dinâmica populacional de uma praga reconhecidamente polífaga, como base para o seu manejo, depende do conhecimento sobre o efeito de espécies vegetais como alimento, na biologia da espécie. Conduziu-se expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
5
17
0
1
Order By: Relevance
“…Suzana et al . () reported that pupal survival with soybean and artificial diet were 56% and 72%, respectively, which are values similar to those obtained in this research. Kunjun et al .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Suzana et al . () reported that pupal survival with soybean and artificial diet were 56% and 72%, respectively, which are values similar to those obtained in this research. Kunjun et al .…”
Section: Discussionsupporting
confidence: 90%
“…Suzana et al . () revealed that the larvae of H. armigera fed only on corn leaves did not complete this stage of growth, whereas those fed on the reproductive parts of wheat showed a survival of 64%, which was similar to the values shown in this research. Amer and El‐Sayed () observed that larva mortality for corn was 48.33%, which was also similar to the value shown in this research.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…) in very extensive management contiguous areas with non-judiciars use of high toxicity pathology category agrochemicals has contributed to resistance development in H. armigera, which resultand in heavy crop losses each year (Vijayabharathi et al, 2014;Specht et al, 2013;Suzana et al, 2015).…”
Section: Introductionmentioning
confidence: 99%